Association Between Atopic Dermatitis and Educational Attainment in Denmark - Schmidt, Sigrun Alba Johannesdottir (JAMA Dermatol, 2021)
IMPORTANCE: Atopic dermatitis (AD) may affect academic performance through multiple pathways, including poor concentration associated with itching, sleep deprivation, or adverse effects of medications. Because educational attainment is associated with health and well-being, any association with a prevalent condition such as AD is of major importance. OBJECTIVE: To examine whether a childhood diagnosis of AD is associated with lower educational attainment. DESIGN, SETTING, AND PARTICIPANTS: This population-based cohort study used linked routine health care data from January 1, 1977, to June 30, 2017 (end of registry follow-up), in Denmark. The study population included all children born in Denmark on June 30, 1987, or earlier with an inpatient or outpatient hospital clinic diagnosis of AD recorded before their 13th birthday (baseline) and a comparison cohort of children from the general population matched by birth year and sex. A secondary analysis included exposure-discordant full siblings as a comparison cohort to account for familial factors. Data were analyzed from September 11, 2019, to January 21, 2021. EXPOSURES: Hospital-diagnosed AD. MAIN OUTCOMES AND MEASURES: Estimated probability or risk of not attaining specific educational levels (lower secondary, upper secondary, and higher) by 30 years of age among children with AD compared with children in the matched general population cohort. Corresponding risk ratios (RRs) were computed using Poisson regression that was conditioned on matched sets and adjusted for age. The sibling analysis was conditioned on family and adjusted for sex and age. RESULTS: The study included a total of 61 153 children, 5927 in the AD cohort (3341 male [56.4%]) and 55 226 from the general population (31 182 male [56.5%]). Compared with matched children from the general population, children with AD were at increased risk of not attaining lower secondary education (150 of 5927 [2.5%] vs 924 of 55 226 [1.7%]; adjusted RR, 1.50; 95% CI, 1.26-1.78) and upper secondary education (1141 of 5777 [19.8%] vs 8690 of 52 899 [16.4%]; RR, 1.16; 95% CI, 1.09-1.24), but not higher education (2406 of 4636 [51.9%] vs 18 785 of 35 408 [53.1%]; RR, 0.95; 95% CI, 0.91-1.00). The absolute differences in probability were less than 3.5%. The comparison of 3259 children with AD and 4046 of their full siblings yielded estimates that were less pronounced than those in the main analysis (adjusted RR for lower secondary education, 1.29 [95% CI, 0.92-1.82]; adjusted RR for upper secondary education, 1.05 [95% CI, 0.93-1.18]; adjusted RR for higher education, 0.94 [95% CI, 0.87-1.02]). CONCLUSIONS AND RELEVANCE: This population-based cohort study found that hospital-diagnosed AD was associated with reduced educational attainment, but the clinical importance was uncertain owing to small absolute differences and possible confounding by familial factors in this study. Future studies should examine for replicability in other populations and variation by AD phenotype.